Decentralized coordinated control of continuous multi-zone objects - Dubovoi, V.; Yukhymchuk, M. (Energy and Automation, 2023)
Distributed continuous multi-zone objects are widespread both in production and in everyday life. Centralized and hierarchical control systems have a rigid relationship structure and are difficult to scale. This complicates their application to objects with frequent and rapid changes in its structure and requirements. The authors have proposed a new approach to the decentralized coordination of control of multi-zone thermal objects, however, the problem of coordination control of the state of continuous multi-zone distributed objects with a dynamic structure and variable requirements has not yet been effectively solved. The aim of the work is to generalize the approach to decentralized coordination of control of distributed systems with multi-zone objects of continuous type. The results of the work are based on the methods of the automatic control theory, heat engineering and simulation modeling. The methodology of decentralized coordination control, in particular the model of the distributed control system of a multi-zonal continuous object, the method of decentralized coordination based on the global-local criterion, the principle of close action, the approaches to active and passive identification of system parameters, the method of forecasting the state of the system based on analysis of spatial-time spectrum of object states were generalized in the work. Based on theoretical studies, a decentralized indoor microclimate control system was proposed. Further research is expected to be directed to the tasks of decentralized coordination by non-linear objects and to the expansion of the scope of practical application of decentralized coordination.Key words: decentralized coordination, multi-zonal objects, principle of close action, local-global criterion